Equality Enhancing Benefit Cut - Possible, but Unlikely - Mauri Kotamäki (Aboa Centre for Economics (ACE), 2020)
This paper considers whether a replacement rate cut can be income equality enhancing and with what conditions. The logical answer to the question is yes, if the propensity of moving from low income state to high income state is high enough. The main contribution of this paper is to derive an analytical expression of income equality improving elasticity. It specifies the limit, after which replacement rate cut is equality enhancing measured by Gini coefficient.
Keywords: J20; D31; J65; 330; Income Equality; Income Distribution; Unemployment Benefits; Gini coefficient